First you need to rewrite the trinomial to read b^2-7b+6.
Then, factor the trinomial. Find two numbers with a product of 6, and a sum of 7.
These two numbers are 6 and 1, but because the 7 in the original problem is negative, you'd need to use -6 and -1.
(b-1)(b-6)=0
b-1=0 or b-6=0
b=1 or b=6
plug the answers into the original problem, and they both work :)
sorry this wasn't explained too well :)
2006-12-10 09:42:52
·
answer #1
·
answered by Anonymous :) 5
·
0⤊
0⤋
Is it equal to something or do you want to simplify it?
b^2+6-7b = b^2 -7b -6
if equal to zero, you can factor it and solve
b^2 -7b +6 = 0
(b - 6)(b - 1) = 0
solve
divide both sides by (b - 1) to get
(b-6) = 0
b -6 + 6 = 0 +6
b=6
divide both sides by (b - 6) to get
(b-1) = 0
b -1 + 1 = 0 +1
b=1
answers b=1 and b=6
checking
substitute b=1
b^2 -7b +6 = 0
1^2 -7(1) +6 = 0
1 -7 +6 = 0
0 = 0 so b=1 is a valid solution
substitute b=6
b^2 -7b +6 = 0
6^2 -7(6) +6 =0
36 - 42 +6 =0
0=0 so b=6 is also a valid solution
final answer b=1, b=6
2006-12-10 09:44:08
·
answer #2
·
answered by rm 3
·
0⤊
0⤋
rearrange
b^2 -7b + 6
factor out
(b - 6)(b - 1)
b=6, b= 1
2006-12-10 09:40:40
·
answer #3
·
answered by rod_dollente 5
·
0⤊
0⤋
b^2 + 6 - 7b = b^2 - 7b + 6
=(b -6)(b -1)
To check: expand (b-6)(b-1) using FOIL.
2006-12-10 09:41:33
·
answer #4
·
answered by S. B. 6
·
0⤊
0⤋
b^2- 7b + 6 = 0
1. (b-6)(b-1) = 0
2. b = 6,1
2006-12-10 10:04:02
·
answer #5
·
answered by James 1
·
0⤊
0⤋